Keterlibatan Stakeholder dalam Penyusunan Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Padang Pariaman - Permata Muspita, Cici; Yusran, Rahmadani (PUBLICNESS: Journal of Public Administration Studies, 2024)
Inclusive policies from a democratic perspective is an issue that has received important attention from various public policy scientists. Specifically, one of the stakeholder engagement forums in Indonesia is called the Development Planning Conference (Musrenbang). Musrenbang is the first step in preparing the Regional Medium Term Development Plan. The main objective of this musrenbang is to accommodate and prioritize activities based on community needs obtained from deliberations. This research is a documented case study which aims to determine stakeholder involvement and obstacles in preparing the RPJMD. The results of this research are that Padang Pariaman Regency has made positive efforts to involve stakeholders in the process of policy formulation and development planning. Even though various efforts have been made to involve stakeholders, there are still obstacles related to the active involvement of various parties. Lack of understanding and enthusiasm for regional development is one of the inhibiting factors in active stakeholder participation. Knowing the obstacles faced in stakeholder involvement in the RPMJD to fulfill the aspirations of the program to be implemented optimally. It is important to strengthen the capacity of stakeholders regarding planning so that they have a deeper understanding of development issues and the planning process. By strengthening involvement and collaboration with various stakeholders, it is hoped that the Padang Pariaman Regency development plan can be more responsive to community needs and support sustainable development and have a positive impact on all levels of society.